On Understanding Religion: A Study of Abdul Karim Soroush’s Thoughts - Anshori, Muhammad - (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
This paper discussed the method of understanding religion according to the views of Abdul Karim Soroush. The main question of this paper is “What is the adequate method to understand religion according to Abdul Karim Soroush?”, and “How to do that?